2016
DOI: 10.1073/pnas.1523817113
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk among flesh-eatingAeromonas hydrophilastrains in mixed infection leading to necrotizing fasciitis

Abstract: Necrotizing fasciitis (NF) caused by flesh-eating bacteria is associated with high case fatality. In an earlier study, we reported infection of an immunocompetent individual with multiple strains of Aeromonas hydrophila (NF1-NF4), the latter three constituted a clonal group whereas NF1 was phylogenetically distinct. To understand the complex interactions of these strains in NF pathophysiology, a mouse model was used, whereby either single or mixed A. hydrophila strains were injected intramuscularly. NF2, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
106
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 23 publications
(31 reference statements)
0
106
0
1
Order By: Relevance
“…Interestingly, in some cases, strain diversity of pathogens within a mixed infection may augment the corresponding disease. This outcome was demonstrated in a necrotizing fasciitis model with two Aeromonas hydrophila strain types that occupied distinct niches within the host, with one strain exhibiting increased virulence due to the secretion of exotoxin A by the other strain (43).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, in some cases, strain diversity of pathogens within a mixed infection may augment the corresponding disease. This outcome was demonstrated in a necrotizing fasciitis model with two Aeromonas hydrophila strain types that occupied distinct niches within the host, with one strain exhibiting increased virulence due to the secretion of exotoxin A by the other strain (43).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, an antagonistic effect through direct and host-mediated elimination was shown. In parallel, authors have observed a synergistic effect on the dissemination via local tissue barrier damage (Ponnusamy et al, 2016). …”
Section: Fields Impacted By the Multi-cellular Behavior Of Aeromonasmentioning
confidence: 96%
“…The exact mechanism of pathogenicity and aeromonads interactions during mixed infections remains unsolved, but intercellular communication likely plays a critical role in cooperation and/or competition behaviors. Ponnusamy et al (2016) have also reported complex cross-talk in which two different clones of A. hydrophila affect each other, leading to a changing course of infection in a murine model. Indeed, an antagonistic effect through direct and host-mediated elimination was shown.…”
Section: Fields Impacted By the Multi-cellular Behavior Of Aeromonasmentioning
confidence: 99%
“…It is the most common opportunistic pathogen found in poikilotherms such as fish, and is also an important human pathogen [3,4]. Different strains of A .…”
Section: Introductionmentioning
confidence: 99%